Cognitive and Neurobehavioral Profile in Boys With Duchenne Muscular Dystrophy. (October 2015) - Banihani, Rudaina; Smile, Sharon; Yoon, Grace; Dupuis, Annie; Mosleh, Maureen; Snider, Andrea; McAdam, Laura
Duchenne muscular dystrophy is a progressive neuromuscular condition that has a high rate of cognitive and learning disabilities as well as neurobehavioral disorders, some of which have been associated with disruption of dystrophin isoforms. Retrospective cohort of 59 boys investigated the cognitive and neurobehavioral profile of boys with Duchenne muscular dystrophy. Full-scale IQ of < 70 was seen in 27%; learning disability in 44%, intellectual disability in 19%; attention-deficit/hyperactivity disorder in 32%; autism spectrum disorders in 15%; and anxiety in 27%. Mutations affecting Dp260 isoform and 5'untranslated region of Dp140 were observed in 60% with learning disability, 50% intellectual disability, 77% with autism spectrum disorders, and 94% with anxiety. No statistically significant correlation was noted between comorbidities and dystrophin isoforms; however, there is a trend of cumulative loss of dystrophin isoforms with declining full-scale IQ. Enhanced psychology testing to include both cognitive and neurobehavioral disorders is recommended for all individuals with Duchenne muscular dystrophy.